Strategi Manajemen Pemasaran Pendidikan Dalam Meningkatkan Minat Calon Peserta Didik Baru Di Madrasah Aliyah Raudlotul Huffadz Kediri Tabanan Tahun Pelajaran 2021/2022 - Syafi`ullah, Alfian; Qosim, Achmad; Sudarsono, Sudarsono (STAI Denpasar Bali, 2021)
Educational marketing management strategy is a social and managerial process by which individuals and groups obtain what they need and want through creating and exchanging and utilizing services. The focus of this research is; 1) What are the efforts in implementing educational marketing management strategies in increasing the interest of prospective new students at Madrasah Aliyah Raudlotul Huffadz Kediri Tabanan? 2) What are the obstacles faced and solutions that can be done in implementing the marketing management strategy of education in increasing the interest of prospective new students at Madrasah Aliyah Raudlotul Huffadz Kediri Tabanan? The objectives of this research are; 1) To find out the efforts in implementing educational marketing management strategies in increasing the interest of prospective new students at Madrasah Aliyah Raudlotul Huffadz Kediri Tabanan. 2) To find out what the obstacles are and the solutions that can be done in the application of educational marketing management strategies in increasing the interest of prospective new students at Madrasah Aliyah Raudlotul Huffadz Kediri Tabanan. This research is a type of qualitative research using a descriptive approach. Data collection was carried out by interview, observation, and documentation methods. So from the results of this study the authors can conclude that planning, implementing and evaluating education marketing management strategies at Madrasah Aliyah Raudlotul Huffadz Kediri Tabanan for the 2021/2022 academic year in order to increase the interest of prospective new students can run well. This happens because of the support of all parties and enthusiasm in the marketing process. The obstacle is the limited number of experts in managing the website and the solution is to find/add experts in managing the Madrasah Aliyah Raudlotul Huffadz Kediri Tabanan website.